Effects of erythropoietin on osteoblast in the tooth extraction socket in mice periodontitis model - Bae, Ju-Eun; Hwang, Sung-Min; Aryal, Yam Prasad; Kim, Tae-Young; Sohn, Wern-Joo; An, Seo-Young; Kim, Ji-Youn; An, Chang-Hyeon; Lee, Youngkyun; Kim, Yong-Gun; Park, Jin-Woo; Lee, Jae-Mok; et al. (Frontiers in Physiology, 2022)
Periodontitis is an excessive inflammatory event in tooth-supporting tissues and can cause tooth loss. We used erythropoietin (EPO), which has been reported to play an important role in bone healing and modulation of angiogenesis, as a therapeutic agent in in vivo and in vitro experimental models to analyze its effect on periodontitis. First, EPO was applied to in vitro MC3T3-E1 cells and human periodontal ligament fibroblast (hPDLF) cells to examine its function in altered cellular events and gene expression patterns. In vitro cultivation of MC3T3-E1 and hPDLF cells with 10 IU/ml EPO at 24 and 48 h showed an obvious increase in cell proliferation. Interestingly, EPO treatment altered the expression of osteogenesis-related molecules, including alkaline phosphatase (ALP), bone morphogenetic protein-2 (BMP-2), and osteocalcin (OC) in MC3T3-E1 cells but not in hPDLF cells. In particular, MC3T3-E1 cells showed increased expression of ALP, BMP-2, and OC on day 5, while hPDLF cells showed increased expression of BMP-2, and OC on day 14. Based on the in vitro examination, we evaluated the effect of EPO on bone formation using an experimentally-induced animal periodontitis model. After the induction of periodontitis in the maxillary left second molars, 10 IU/ ml of EPO was locally applied to the extraction tooth sockets. Histomorphological examination using Masson’s trichrome (MTC) staining showed facilitated bone formation in the EPO-treated groups after 14 days. Similarly, stronger positive reactions against vascular endothelial growth factor (VEGF), cluster of differentiation 31 (CD31), runt-related transcription factor 2 (RUNX2), and osteocalcin (OC) were detected in the EPO-treated group compared to the control. Meanwhile, myeloperoxidase, an inflammatory marker, was decreased in the EPO-treated group on days 1 and 5. Overall, EPO facilitates bone healing and regeneration through altered signaling regulation and modulation of inflammation in the osteoblast cell lineage and to a lesser extent in hPDLF cells.